2022
DOI: 10.3389/fgene.2022.960731
|View full text |Cite
|
Sign up to set email alerts
|

The GNB3 c.825C>T (rs5443) polymorphism and protection against fatal outcome of corona virus disease 2019 (COVID-19)

Abstract: Background and aims: Albeit several factors which influence the outcome of corona virus disease (COVID-19) are already known, genetic markers which may predict the outcome of the disease in hospitalized patients are still very sparse. Thus, in this study, we aimed to analyze whether the single-nucleotide polymorphism (SNP) rs5443 in the gene GNB3, which was associated with higher T cell responses in previous studies, might be a suitable biomarker to predict T cell responses and the outcome of COVID-19 in a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(26 reference statements)
0
2
0
1
Order By: Relevance
“…The ACE2 rs2285666 GG genotype or G-allele were associated with an almost twofold increased risk of infection and a threefold increased risk of a severe or fatal outcome of COVID-19 (15). We also demonstrated that the GNB3 c.825C>T (rs5443) TT genotype is protective against COVID-19 fatality (16).…”
Section: Introductionmentioning
confidence: 57%
“…The ACE2 rs2285666 GG genotype or G-allele were associated with an almost twofold increased risk of infection and a threefold increased risk of a severe or fatal outcome of COVID-19 (15). We also demonstrated that the GNB3 c.825C>T (rs5443) TT genotype is protective against COVID-19 fatality (16).…”
Section: Introductionmentioning
confidence: 57%
“…Die Variabilität der COVID-19-Verläufe erschwert die klinische Beurteilung, insbesondere wenn es darum geht, Risikopatienten für eine schwere Erkrankung frühzeitig zu erkennen. Eine Vielzahl potenzieller Risikofaktoren für einen schweren COVID-19-Verlauf konnte identifiziert werden [ 3 ]. Dazu gehören insbesondere hohes Patientenalter und Vorerkrankungen wie chronische Nierenerkrankung, Diabetes, arterielle Hypertonie oder Immunsuppression [ 4 , 5 ].…”
unclassified
“…Regarding the genetic background, several reports have shown a link between the genetic background and the immunological response following COVID-19 or vaccination. [8][9][10] However, there are no clear data showing a relation between the tendency for RA flares following vaccination and a particular genetic background. Despite differences in the genetic background, at least comparable results have been reported in Japanese 2 and other ethnic groups.…”
mentioning
confidence: 99%